(untitled) (The Conference Hub, 2025)
The rapid progress of biotechnology, genetic engineering, artificial intelligence and modern medical systems is reshaping the foundations of human life, health and social responsibility. These developments create new ethical dilemmas that require interdisciplinary reflection and globally coordinated responses. This article examines the contemporary relevance of bioethics as a normative framework for guiding scientific innovation while safeguarding human dignity. It explores global issues such as bioterrorism, ecological degradation, pandemics, genetic technologies and widening inequalities, tracing how these challenges reshape the moral landscape of medicine and public health.